Lncrna FGD5-AS1 Aggravates Myocardial Ischemia-Reperfusion Injury by Sponging Mir-129-5p - Peng Wei; Zhifeng Dong; Ming Lou (Tehran University of Medical Sciences, 2022)
Background: LncRNA FGD5-AS1 regulates the pathogenesis of many human diseases. We aimed to elucidate the function of lncRNA FGD5-AS1 and the regulatory mechanism of lncRNA FGD5-AS1/miR-129-5p in myocardial ischemia-reperfusion (I/R) injury. Methods: Myocardial I/R injury mice model and H/R treated H9c2 cells were established. RT-qPCR and Western blot analysis were used to detect the mRNA and protein expression. Cell viability was detected by MTT assay. Dual luciferase reporter assay was applied to confirm the relationship between lncRNA FGD5-AS1 and miR-129-5p. Results: LncRNA FGD5-AS1 was upregulated in myocardial I/R injury mice models and H/R treated H9c2 cells. Functionally, knockdown of lncRNA FGD5-AS1 promoted cell viability and inhibited apoptosis in H/R treated H9c2 cells. In addition, lncRNA FGD5-AS1 directly targets miR-129-5p. Upregulation of lncRNA FGD5-AS1 weakened the protective effect of miR-129-5p on myocardial I/R injury. Conclusion: LncRNA FGD5-AS1 aggravates myocardial I/R injury by downregulating miR-129-5p.